Implementing the Concept of Integration of Science and Islamic Values at Islamic University - Agus Budiyono; Abd Haris; Linda Tri Antika; Arin Wildani (AL-ISHLAH: Jurnal Pendidikan, 2024)
The integration of scientific principles within Islamic religious universities governed by the Ministry of Religion is a widespread practice. However, the application of this concept across universities offering programs under the auspices of both the Ministry of Education and the Ministry of Religion remains unexplored. This study delineates the framework for integrating scientific knowledge at an Islamic University in Madura, focusing on the execution and assessment of education that amalgamates scientific insights and Islamic values. Employing observational techniques on policy documents and teaching resources of instructors, alongside semi-structured interviews with fifteen educators from the physics, biology, and mathematics departments, this investigation reveals a unique five-pillar knowledge integration concept. These pillars encompass Islam, Indonesia, Islamic Boarding School, Madura, and Aswajaan perspectives. The formal documentation supporting this integration at Madura Islamic University is encapsulated within its Statutes and chancellor's guidelines for curriculum enhancement. Evidence of implementation is observed in instructors' Syllabi and teaching materials, albeit only 53.3% have successfully linked scientific content with Qur'anic verses. The primary challenge identified is the considerable time required to develop materials that effectively integrate Islamic values. Solutions proposed include the creation of a comprehensive guide for integrating the five knowledge pillars and extensive training for all faculty members to facilitate this integration process.